Model Pengukuran Kinerja pada Perusahaan Jasa Konstruksi di Kota Banjarmasin - Mentayani, Ida (Universitas Brawijaya, Indonesia, 2012)
The research aims to describe performance measurement model on construction service companiesin Banjarmasin. The object are 80 medium scale and small scale companies. Based on the research, ithas been known that used as performance measurement based on the financial statement. Types of financialstatement that used as performance measurement sources are balance sheet, income statement,statement ofchanges in equity and cash flow statement. In utilizing the financial statements for the assessment of performanceusing ratio analysis of liquidity, solvency, profitability and activity. To declare that the ratio -financial ratios illustrate the performance of construction services company, with a good or bad performancecriteria then the ratio should be compared with the ratio of industry standards. Performance measurementmodel base on financial statements has some weakness, including less relevancy aspect, orientedon past performances, short term oriented, less flexibility, non spuring improvement and ambiguous on costaspects.